An introduction to the New Testament manuscripts and their texts - Parker, D. C. (David C.) (Cambridge, UK ; New York : Cambridge University Press, 2008)
This introduction to the New Testament provides a thorough grounding in the study and editing of the New Testament text combined with an emphasis on the dramatic developments in the field. It covers ancient sources in Greek, Syriac, Latin and Coptic and describes the manuscripts and other ancient textual evidence.
Part III, The sections of the New Testament: 7. The Book of Revelation -- 8. Paul -- 9. Acts and the Catholic epistles -- 10. The Gospels -- 11. Final thoughts.
Includes bibliographical references and indexes.
Print version record.
Master record variable field(s) change: 630
Keywords: Bible. -- Manuscripts; Bible; Bibel; RELIGION -- Biblical Studies -- New Testament; Textkritik; Textgeschichte; Electronic books; Manuscripts